A Case of Extra-axial Cavernous Angioma Originating from the Oculomotor Nerve - Inui, Toshitaka; Hashimoto, Hiroyuki; Fujimoto, Kenta; Shimokawara, Tateo; Nishiguchi, Mitsuhisa; Yokoyama, Syohei; Omoto, Koji; Matsuoka, Ryuta; Yaegaki, Takahide (Indian Journal of Neurosurgery, 2016)
We report a case of extra-axial cavernous angioma, which originated from the oculomotor nerve and, by hemorrhaging, resulted in oculomotor nerve palsy. Cavernous angioma generally occurs in the brain parenchyma. Therefore, this case is extremely rare. We believe that preoperative sequential magnetic resonance imaging contributed to preoperative diagnosis in this case.
Keywords: cavernous angioma; extra-axial; oculomotor nerve; magnetic resonance imaging